Social media and scientific research are complementary-YouTube and shrikes as a case study - Dylewski, Łukasz; Mikula, Peter; Tryjanowski, Piotr; Morelli, Federico; Yosef, Reuven (Die Naturwissenschaften, 2017)
Fascination with animals and their behaviour is one the most prominent patterns persisting in all human cultures. During the last decades, however, technological development and public access to the Internet have increased the speed and the extent of information sharing at an unprecedented rate, in some cases even challenging the traditional methods used in science. In order to understand the extent of this influence, we focused on the behaviour of shrikes. Shrikes are an enigmatic group of songbirds with a unique behaviour of impaling prey. We employed an extensive Internet search on YouTube (YT), a very popular and increasingly important source of information worldwide, for videos recording shrikes. Our analyses revealed that the number of shrike videos on YT is strongly positively correlated with classical knowledge on shrikes from books and scientific articles. Our results also suggest that in some cases YT may provide an alternative source of information on shrike ecology and behaviour. YT videos may thus provide new insights into the study of certain species or subjects and help identify gaps in ecological studies, especially in poorly studied species.
Keywords: internet; Passeriformes; Behavior, Animal; Video Recording; Shrikes; Social media; Animals; výzkum; Citizen science limits; sociální média; Internet; zvířata; Behaviour; Research; chování zvířat; Social Media; audiovizuální záznam